Synthesis of Propylene Carbonate from Carbon Dioxide and Propylene Oxide Using Zn-Mg-Al Composite Oxide as High-efficiency Catalyst - Dai, Wei-Li; Yin, Shuang-Feng; Guo, Rui; Luo, Sheng-Lian; Du, Xin; Au, Chak-Tong (Catalysis letters, 2010)
A series of Zn-Al composite oxides that were modified with alkaline earth metals, Zn-M-Al-O (M = Mg, Ca, Sr, and Ba) were fabricated via calcination of the corresponding hydrotalcite precursors, and evaluated as catalysts for the synthesis of propylene carbonate (PC) from CO₂ and propylene oxide. Among the Zn-M-Al-O catalysts, Zn-Mg-Al-O (Zn/Mg = 4.0, pH = 10, without hydrothermal treatment) is the best in performance, showing PC selectivity of 99.2% and yield of 88.8% (140 °C, 12 h). Furthermore, the Zn-Mg-Al-O catalyst can be readily reused and recycled without any loss of activity in a test of five cycles. Through detailed studies of the basic nature of the Zn-M-Al-O catalysts, it was found that a moderate basicity (6.1 ≤ H ₀ < 8.9) is beneficial to the cycloaddition reaction. The NH₃- and CO₂-TPD results also indicate that the Zn-Mg-Al-O catalyst has acid-base bifunctional properties, and a reaction mechanism is proposed. Graphic Abstract Zn-Mg-Al composite oxides were prepared via calcination of the corresponding hydrotalcite precursors, and used as catalysts for the synthesis of propylene carbonate from CO₂ and propylene oxide. We achieved high catalytic efficiency under mild conditions, easy separation of catalyst from the product, and good recyclability of the catalyst. A plausible reaction mechanism has been proposed for the catalytic action. [graphic removed]